Index of Orthodontic Treatment Need (IOTN) for Libyan Children in Benghazi: An ep- idemiological survey on school children in Benghazi city - Abraheem, Mubarakah; Mohamed, Mahfud (Libyan Journal of Dentistry, 2020)
Background: malocclusion is a common oral health problem that can affect the psychosocial well-being in the long term. Many indices were developed to prioritize patients so that those who have the greatest need receive treatment. Objectives: this study was aimed to assess the orthodontic treatment need of Libyan children using index of orthodontic treatment need (IOTN). Methods: Total of 511 students (260 females, 251 males) consti- tuted the sample, which was randomly selected from age group of 12-14 years in Benghazi public schools. The dental health component (DHC) of IOTN was applied to assess orthodontic need, whereas the aesthetic com- ponents (AC) of IOTN along with a questionnaire were used to evaluate participants’ perception towards their own orthodontic status. Results: the majority of participants (79. 5%) displayed smile satisfaction, with gen- der difference (p<0. 05). Satisfaction with teeth appearance was showed by 39. 7% of the respondents while 60. 3% of the participants were dissatisfied, owing dissatisfaction to various reasons such as color of their teeth (9%) and teeth arrangement (34. 8%). More than half of respondents (55%) considered well arrangement of teeth is crucial for overall facial appearance. According to ac there was a strong agreement between researcher and respondents in treatment need. The researcher found 10% were definitely needed treatment against 6. 2% found by self-perceived need; the researcher categorized 71.4% of the respondents as no treatment need against 71. 4% found by self-perceived need. Conclusions: most of the children in Benghazi`s public schools are satisfied with teeth appearance. Most of the public schools children in Benghazi need no/slight orthodontic treatment need. Age, gender and socioeconomic were not influencing factors affecting orthodontic treatment need among Libyan children in Benghazi.